2012
DOI: 10.1002/fes3.5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a serine carboxypeptidase increases carpel number and seed production in Arabidopsis thaliana

Abstract: Seed production is an ultimate component of crop yield. Increasing seed production has long been a pursuit for crop breeders and is an indisputable measure of food safety. Advances in biotechnology can provide novel means to achieve increased seed production by genetic engineering. Overexpression of ECS1 (Extra Carpels and Seeds), a gene encoding a serine carboxypeptidase, partially suppresses the leaf phenotypes of mutant bri1‐5, a weak allele of brassinosteroid‐insensitive 1 (BRI1). Moreover, overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
5
19
2
Order By: Relevance
“…However, we saw no visible phenotypes with the BRS1 knockdown mutant, brs1-1 ( Fig. 1), consistent to no significant phenotype was observed in BRS1 mutant [4][5][6][7].…”
Section: Seedling Developmental Phenotypes Of Brs1supporting
confidence: 77%
See 2 more Smart Citations
“…However, we saw no visible phenotypes with the BRS1 knockdown mutant, brs1-1 ( Fig. 1), consistent to no significant phenotype was observed in BRS1 mutant [4][5][6][7].…”
Section: Seedling Developmental Phenotypes Of Brs1supporting
confidence: 77%
“…Its overexpression can rescue the receptor mutant of brassinosteroid (BR), bri1-5, indicating BRS1 might play an important role in BR signaling [4,5]. BRS1 has five close homologs, of which three can suppress bri1-5 developmental defects [6]. In contrast, no significant phenotypes have been identified in single or double mutants of either BRS1 or its homologs [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggested SCPL proteins might work in biochemical pathways and be vital for normal plant growth and development, for the synthesis of compounds that protect plants against pathogens and ultraviolet rays, and for resistance to natural and manmade xenobiotics (Milkowski and Strack ). ECS1 (Extra Carpels and Seeds) over‐expressing Arabidopsis showed sensitivity to BR too (Wen et al ). The Sad7 gene could also resist soil‐borne pathogens, so as to better protect plants.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al () suggested that SCP46 was a master regulator of grain filling and seed germination, possibly via participating in the ABA signaling, and the GS5 gene played a positive role in regulating grain size (Li et al ). The thousand‐grain weight of the ECS1 over‐expressing plant seed increased by about 33% compared with the wild‐type (Wen et al ). Additionally, NtSCP1 and NtSCP2 controlled the cell elongation (Bienert et al ).…”
Section: Introductionmentioning
confidence: 99%